Seasonal Variability in the Composition of Particulate Matter and the Microclimate in Cultural Heritage Areas - Cristiana Radulescu; Claudia Stihi; Rodica-Mariana Ion; Ioana-Daniela Dulama; Sorina-Geanina Stanescu; Raluca Maria Stirbescu; Sofia Teodorescu; Ion-Valentin Gurgu; Dorin-Dacian Let; Liviu Olteanu; Nicolae-Mihail Stirbescu; Ioan-Alin Bucurica; et al. (Atmosphere, 2019)
This study is the first attempt to decipher the effect of particulate matter (PM) composition on people’s health and on historic sites, in correlation with the daily and seasonal microclimate monitoring of the indoor and outdoor areas of the Roman Mosaic Edifice museum (the maritime port of Constanta, Romania). More specifically, the increase of metal concentrations in particulate matter during the summer of 2018 and spring of 2019 in the museum under investigation could possibly be associated with the microclimates of both seasons, with coastal factors, as well as with the anthropic activities specific to the port of Constanta. FTIR and inductively coupled plasma mass spectroscopy (ICP-MS) techniques, used for the investigation of PM2.5−10 samples, revealed high concentrations of Fe, Al-rich, and soluble particles inside the investigated museum area. In this respect, the chemical measurements of the PM2.5−10 masses highlighted high concentrations of heavy metals (i.e., Al, Fe, Zn, Mn, and Pb) and low concentrations of trace metals (i.e., Cr, Ni, Cu, and Cd). Statistical analysis showed that the chemical compositions of the particulate matter in the indoor and outdoor areas of the Roman Mosaic Edifice were influenced by microclimatic conditions, mainly temperature and relative humidity (RH). A potential health risk for tourists is the thermal and humid conditions, alongside the toxic components of the particulate matter. This research seeks to provide solutions for improving the environmental conditions inside the Roman Mosaic Edifice and to offer useful suggestions concerning health promotion and the protection of museum exhibits against possible future deterioration.